High performance of ethanol co-laminar flow fuel cells based on acrylic, paper and Pd-NiO as anodic catalyst. (20th July 2016) - López-Rico, C.A.; Galindo-de-la-Rosa, J.; Ortiz-Ortega, E.; Álvarez-Contreras, L.; Ledesma-García, J.; Guerra-Balcázar, M.; Arriaga, L.G.; Arjona, N.
Graphical abstract: Pd-NiO nanoparticles obtained from a green reduction method were used in direct ethanol membraneless co-laminar flow fuel cells as a cleaner technology for energy conversion Highlights: Pd-NiO was successfully synthesized by an effective fast and low cost green method. Pd-NiO showed 16-fold higher current density than Pd nanoparticles. The acrylic LFFC with 14.29 cm 3 total volume showed 108 mW cm −2 in performance. Paper LFFC with 0.62 cm 3 resulted in 85.5 mW cm −2 in performance. Abstract: Ethanol co-laminar flow fuel cells operating at room temperature have rarely been reported, primarily due to problems associated with the kinetics of ethanol oxidation. In this work, we present a study of the effect of ethanol concentration, pH of anodic and cathodic streams, and nature of the oxidant on the performances of an acrylic cell and a paper-based, membraneless co-laminar flow fuel cell (LFFC), with total cell volumes of 14.29 cm 3 and 0.62 cm 3, respectively. Additionally, this work reports the synthesis of a Pd-NiO anodic nanocatalyst by a simple, fast, and environmentally friendly method in order to match the clean, easy-to-use, and simple fabrication methods of these ethanol co-laminar flow fuel cells. The synthesized Pd-NiO exhibited a crystallite size of 8.1 nm and an average particle size of 8.7 nm for Pd-NiO/C. The highest performances were obtained by combining an alkaline anodic stream with an acidic cathodic stream, increasing the cell voltage, and decreasing cathodic limitations caused by the simultaneous occurrence of oxygen reduction as well as hydrogen reduction reactions. With these improvements, power densities of 108 and 85.5 mW cm −2 were obtained for the acrylic and the paper-based co-laminar flow fuel cell, respectively, which are the highest values reported to date for ethanol LFFCs at room temperature.